Traditional indigenous values of ethno-botanical plants preserved in selected sacred groves of the Almora District (Western Himalayas), Uttarakhand, India - Durgapal, Medha; Kumar, Mukesh; Arya, Ashish Kumar (Ethnobotany Research and Applications, 2024)
Background: The current study primarily focused on documentation and identification of ethno-botanical plants utilized by local inhabitants in sacred groves of the Kumaon Himalayas. These plants are traditionally used by the indigenous communities of the region to treat various ailments. Methods: The present study is based on extensive and frequent field surveys conducted in sacred groves of the Kumaon Himalayas. The respondents were interviewed using a semi-structured questionnaire and group discussions. Microsoft Excel was used for the analysis of the collected data. Results: A total of 70 traditionally used ethno-botanical plant species belonging to 64 genera and 41 families were identified in the present study. Asteraceae was the most predominant family in the study area, followed by Fabaceae and Rosaceae. Sixty medicinal plant species are utilized to cure 19 major ailments. Different plant components, including leaves (53%), roots (27%), and bark (8%), are known to be utilized for treating various illnesses. Conclusions: The impact of modernization and growing disbelief in traditional value systems among the young generation has impacted the preservation of sacred groves. Sacred groves are home to many wild but valuable plant species and play a significant role in restoring the original germplasm of the species. Understanding the traditional knowledge system of residents and communities in the Himalayan region could help and promote conservation practices for the sustainable use of medicinal species. Keywords: Ailments, Conservation, Indigenous people, Sacred groves, Traditional knowledge